Computing method for periodic stream reservation in TSN combined with SDN controller - Jianzhong SU; Huayu ZHANG; Hailong ZHU (Tongxin xuebao)
In recent years, with the development of TSN, its low latency, low jitter and predictable maximum delay can be widely used in automatic driving technology and industrial Internet.To solve the 75% (empirical value) bandwidth problem of stream reservation technology in TSN protocols, and combine with the separation of data plane and control plane in SDN, a stream reservation solution was put forward, which was combined with TSN-SDN controller and scheduling the transmission path and reservation of the entire topology in the control plane.And two reservation computing methods was put forward, which would give out a bandwidth with time slot.The simulation experimental results show that it can control the jitter to 0 based on require latency, and also use the bandwidth based on time slot to guarantee the utilization of bandwidth.